Academic Excellence Paradox: Self-Imposed Academic Pressure and Well-Being Among Gen-Z Students in a HyFlex Learning Environment - Dela Cruz, Rafya Jose P.; Jose, Johanna Louise C.; Paraon, Raichel Joy R.; Arcinas, Myla M. (Future Science / FSH-PH Publications, 2025)
This correlation study examined the complex interrelationship between self-imposed academic pressure, academic performance, and multidimensional well-being among high-achieving undergraduate students (N = 101, 57.7% response rate) at a premier private university in Manila, Philippines. Through rigorous purposive sampling based on established honors criteria (GWA ≥ 3.0), the study implemented a comprehensive online assessment instrument measuring three primary constructs. Findings revealed pronounced levels of self-imposed academic pressure (Mdn = 6.0 on a 7-point scale, interpreted as High), with academic performance anxiety (Mdn = 7.0, Very High) and future career impact concerns (Mdn = 7.0, Very High) emerging as predominant stressors. Academic achievement metrics demonstrated exceptional performance, with a median GPA of 3.5 and 53.27% of participants attaining GPAs of 3.50 or higher. Despite respondents reporting robust scores across physical (Mdn = 5.5, High), psychological (Mdn = 6.5, High), and social well-being domains (Mdn = 6.0, High), the Spearman Rho test uncovered significant bidirectional relationships. Self-imposed academic pressure exhibited a weak positive correlation with academic performance (r = 0.327, p < 0.01), explaining approximately 10.7% of the variance in GPA (r² = 0.107), suggesting that heightened personal standards confer modest performance advantages. However, a more pronounced moderate negative correlation emerged between self-imposed pressure and overall well-being (r = -0.436, p < 0.01), with particularly strong adverse effects on academic confidence (r = -0.478, p < 0.01), interpersonal relationship satisfaction (r = -0.467, p < 0.01), and cognitive function (r = -0.456, p < 0.01). The differentiated impact across pressure dimensions—with social comparison processes enhancing performance (r = 0.384, p < 0.01) while coursework management difficulties undermining it (r = -0.412, p < 0.01)—illuminates a fundamental academic paradox wherein self-imposed pressure simultaneously enhances performance metrics while compromising holistic well-being. These findings underscore the imperative for educational institutions to develop balanced academic approaches and targeted support systems that foster both achievement and wellness in HyFlex learning environments, particularly addressing the psychological, social, and physical dimensions most adversely affected by academic pressure.